Smart sensor for automatic drip irrigation system for paddy cultivation. (January 2019) - Barkunan, S.R.; Bhanumathi, V.; Sethuram, J.
Abstract: Agriculture needs 85% of the available freshwater and its requirement may increase in future. Hence, a system is needed to utilize water efficiently in agriculture. The modern drip irrigation system lessens a significant amount of water usage compared to the traditional methods. And some crops need variable amounts of water as it grow e.g. paddy. This paper proposes an automation of drip irrigation in which the smartphone initially captures soil image, calculates its wetness level and transmits the data onto the microcontroller through GSM module intermittently. The microcontroller decides the irrigation and sends the status of the field to the Farmer's mobile phone. The system is tested for paddy field for over a period of three months. It is observed from the experimental setup, that it saves nearly 41.5% and 13% of water compared to the conventional flood and drip irrigation methods respectively.